Allowing time for 8+ hours of sleep: identification and validation of important beliefs using the reasoned action approach - Tagler, Michael J. (Frontiers in Psychology, 2024)
The present studies advance research using the Reasoned Action Approach (RAA) to understand sleep behavior. Belief elicitation and follow-up validation studies were conducted to identify readily accessible and important beliefs regarding allowing time for 8+ hours of sleep each night. Identification of beliefs is necessary to understand the attitudes, perceived normative pressure, and perceived behavioral control (PBC) that individuals hold told the behavior. Important attituderelevant beliefs included positive effects on mood, thinking, health, and productivity. Important normative beliefs were perceived injunctive pressure from family, health professionals, and significant others. Because of the strong influence of PBC on intentions/behavior, most important were control beliefs about the need for good time management. Identification of these key beliefs is a necessary step toward the design of effective interventions to improve sleep duration.